POTENSI GURU KREATIF: OPTIMALISASI PERAN DI ERA PEMBELAJARAN DIGITAL DI SMK 1 PASUNDAN KOTA SERANG - Nasrullah, Anton; Jumhana, Enjum; Faturohman, Faturohman; Marlina, Mira; Dwiyanti, Widya (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service activity aims to enhance the digital competency of teachers at SMK 1 Pasundan Kota Serang. In response to the growing need for technology integration in education, this program focused on training teachers to utilize digital platforms and multimedia tools to improve the learning process. The activity consisted of an introductory session on basic digital tools such as Google Classroom and Zoom, followed by advanced training on creating multimedia learning materials. Teachers were also provided with opportunities to practice directly, allowing them to integrate technology into their teaching effectively. The evaluation results showed significant improvement in the teachers' confidence and skills in using digital tools, though some challenges remained, particularly in adapting technology to existing teaching methods. The results of this activity indicate that continuous professional development in digital literacy is essential for teachers to fully optimize the use of technology in education. Further training and follow-up sessions are recommended to address the remaining challenges and deepen teachers’ competencies in digital education